Pengaruh Storytelling Terhadap Berbicara Siswa Subtema 3 Bahasa Indonesia Kelas V SDI Al-Washoya Ngoro Jombang - Widyaningrum, Wahyu; Kamidjan; Fitra Raharja, Hawwin (IJPSE : Indonesian Journal of Primary Science Education, 2021)
This study aimed to determine the effect of the storytelling learning model on students' speaking skill in sub-theme 3; Indonesian Language Competence for grade V at Al-Washoya Ngoro Islamic Elementary School, Jombang. This research used a quantitative research design with experimental research while using one group pre-test and post-test. The population in this study were all students of grade V of Al-Washoya Ngoro Islamic Elementary School which has 15 students. The sample used was the fifth grade students, totaling 15 students who will be experiment class and will be given a storytelling learning model. Based on the data result from pre-test and post-test, it was shown that the students' speaking skills by using storytelling learning model get the sig value of 0.000 <0.05. This result illustrated the effect of the storytelling learning model on students' speaking skills of grade V students at Al-Washoya Ngoro Islamic Elementary School, Jombang for academic year of 2019-2020.